Comparative Efficacy of Three Different Fixed Timed Artificial Insemination Protocols in Sahiwal Cows - Singh, A.; Singh, N.; Brar, P. S.; Malik, V. S.; Singla , G. (The Indian Journal of Animal Reproduction, 2021)
The study evaluated efficacy of three different fixed timed estrus synchronization protocols administered at random stage of estrous cycle in Sahiwal cows. Pluriparous Sahiwal cows (n=30) having normal estrous cycle and genitalia were randomly divided into three groups. Group 1 (Ovsynch group), cows (n=10) were administered standard Ovsynch protocol, Group 2 (Ovsynch + CIDR); cows (n=10) were administered Ovsynch protocol along with intravaginal insertion of CIDR implant on day 0, Group 3 (Estradiol based group); cows (n=10) were injected Estradiol benzoate 2 mg + Cloprostenol 500 µg along with insertion of CIDR on day 0, then Estradiol benzoate 1 mg + Cloprostenol 500 µg + eCG 400 IU (Inj. Folligon 400 IU) on Day 7. CIDR was removed at the time of prostaglandin injection (Day 7) in the group 2 and 3. All the cows were fixed timed inseminated on Day 10 of the protocol. Results revealed that the growth rate of dominant follicle from day 7 to 10 was higher in Estradiol based and Ovsynch + CIDR group than Ovsynch group (1.42±0.14, 1.38±0.13 and 1.13±0.07 mm, respectively). Average size of dominant follicle on day 10 was higher in Ovsynch + CIDR than the Ovsynch and Estradiol based group (11.4±0.48 vs 10.3±0.61 vs 10.2±0.42 mm, respectively). All cows of Ovsynch+ CIDR group underwent ovulation, whereas, 60 percent cows ovulated in the group 1 and 2. The ovulating cows had higher average diameter of preovulatory follicle on day 10 compared to anovulatory cows in the Ovsynch (11.6±0.20 vs 8.4± 0.80 mm, p<0.05) and Estradiol based group (10.5±0.56 vs 9.9±0.66 mm, p>0.05). Higher pregnancy rate was achieved in the Ovsynch + CIDR group compared to Estradiol based and the Ovsynch group (60 vs 40 and 30 percent, respectively). Results showed that Ovsynch + CIDR protocol was more effective on random day of estrous cycle in inducing ovulatory estrus and subsequent fertility compared to the Ovsynch and Estradiol based protocol. It was also concluded that higher diameter of dominant follicle on day 10 and follicle growth rate from day 7-10 favored ovulation and establishment of pregnancy in Sahiwal cows.